Association between dietary fiber intake and suicidal ideation: a cross-sectional survey - Huang, Huaying; Fu, Jianjiong; Lu, Keyu; Fu, Yaming; Zhuge, Pan; Yao, Yu (Frontiers in Nutrition, 2024)
Background: Dietary fiber is beneficial for improving mental health. However, few studies have evaluated the relationship between fiber-rich food and suicidal ideation. Thus, we aimed to assess whether dietary fiber consumption was associated with the risk of suicidal ideation.Methods: Data of 21,865 American adults were retrieved from the National Health and Nutrition Examination Survey (NHANES). Logistic and restricted cubic spline regression analyses were performed in order to evaluate the association of dietary fiber intake with suicidal ideation, as indicated by item nine of the nine-item Patient Health Questionnaire (PHQ-9). These analyses took into consideration several confounding factors that may potentially influence the results.Results: Herein, we detected an L-shaped association between dietary fiber intake and the risk of suicidal ideation. For the most conclusive model, an increase of 1 g/1000 kcal/d in dietary fiber intake was accompanied by a 5% reduction in the risk of suicidal ideation. The inflection point of the L-shaped association was located at 7.8 g/1000 kcal/d. When dietary fiber intake exceeded the above level, the risk of suicidal ideation no longer decreased.Our findings of reduced risk of suicidal ideation in people with higher dietary fiber intake suggest the potential clinical and public health value of dietary fiber.Interventional investigations are warranted to prove whether adhering to a high-fiber diet prevents and reduces suicidality.